Pengembangan Media Pembelajaran Berbasis Audio Visual pada Materi Cerita Pendek untuk Siswa Kelas XI SMK - Simanjuntak, Amaya Tasha; Safina, Nila; Soraya, Ratna (Medan Resource Center, 2025)
This study aims to develop and evaluate the effectiveness of interactive audio-visual learning media for short story materials in 11th-grade vocational school students. Utilizing the Research and Development (R&D) method based on the Borg and Gall model, the research process involved data collection, planning, product development, initial field testing, revisions, and implementation. The findings indicate that the developed media was rated as